2020
DOI: 10.1002/app.50424
|View full text |Cite
|
Sign up to set email alerts
|

Improved CO2/CH4 separation performance of mixed‐matrix membrane by adding ZIF‐7‐NH2 nanocrystals

Abstract: Membrane‐based technology is an attractive alternative in terms of CO2 separation. Pebax‐based membranes are regarded as potential candidates for CO2 separation due to the favorable interaction between its poly (ethylene oxide) chains with CO2 molecules and inorganic fillers. However, the separation performance for CO2/CH4 mixture is still suffered from the moderate gas permeability and selectivity. To overcome this problem, in this work, amino‐functionalized zeolite imidazolate framework (ZIF‐7‐NH2) nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…P. Zhao et al [21] suggested that this gate-opening phenomenon may lead to an increase in CO 2 affinity due to the change in the electrostatic field brought about inside the particles. Several other studies [52,53] have shown that ZIF-7 has such high affinity while interacting with CO 2 that it causes the CO 2 solubility to increase. B.A.…”
Section: Gas Permeation Properties Of Composite Membranesmentioning
confidence: 95%
“…P. Zhao et al [21] suggested that this gate-opening phenomenon may lead to an increase in CO 2 affinity due to the change in the electrostatic field brought about inside the particles. Several other studies [52,53] have shown that ZIF-7 has such high affinity while interacting with CO 2 that it causes the CO 2 solubility to increase. B.A.…”
Section: Gas Permeation Properties Of Composite Membranesmentioning
confidence: 95%
“…This shows that mechanochemical synthesis has successfully opened a new route towards the formation of 100% amino functionalised ZIF-7 crystals (the highest reported loading of the amino group in ZIF-7 crystals synthesised via a mixed-linker strategy using the solvothermal route is 70%). 28,29 This indicates that mechanochemical synthesis can be a possible alternative route to form functionalised crystalline MOF particles not accessible via the normal solvothermal synthesis route. Further characterisation of these amino-functionalised particles can be found in S1d (ESI †).…”
mentioning
confidence: 99%